Analisis Kinerja Keuangan pada PT. Mayora Indah, Tbk Berdasarkan Metode Economic Value Added (EVA) - Merlina Verawati Tasik Bua’; Agustinus Mantong; Grace Sriati Mengga’ (CV. Ulil Albab Corp, 2024)
The research is intended to analyze financial performance at PT. Mayora Indah, Tbk which is listed on the Indonesia Stock Exchange, based on the Economic Value Added method at PT. Mayora Indah, Tbk. Processing PT financial reports. Mayora Indah, Tbk uses quantitative analysis techniques with data analysis methods in the form of numbers which include financial reports at PT. Mayora Indah, Tbk. The data used is secondary data in the form of PT's financial reports. Mayora Indah.Tbk for the 2019-2023 period is secondary data used and obtained via the website www.idx.co.id. The research results show that the financial performance of PT. Mayora Indah, Tbk based on the 2019-2023 EVA method produces a positive EVA value.